1994
DOI: 10.1093/ageing/23.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Visual Problems amongst Residents of Part III Homes

Abstract: A survey of visual function and ophthalmic pathology of 100 residents of three residential homes for elderly people was carried out in Lambeth London. The main pathologies were cataracts detected in half of the subjects (6% were referred for extraction) and chronic simple glaucoma in 17%. Unrecognized significant refraction errors were found in 34% of subjects. Only eight of the 14 residents eligible for blind or partially sighted registration had been already registered. It is suggested that old people enteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…This is not unexpected particu larly when the numbers from nursing homes and residual homes were so small, thereby making analysis less robust. However, in the recently reported survey by Sturgess et al [4] on the ocular pathology in elderly residents in old peoples homes the authors reported prev alence rates of 51% for cataract and 18% for glaucoma. Their screening methods were dif ferent from those employed in this study and in addition they included cognitively im paired residents.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is not unexpected particu larly when the numbers from nursing homes and residual homes were so small, thereby making analysis less robust. However, in the recently reported survey by Sturgess et al [4] on the ocular pathology in elderly residents in old peoples homes the authors reported prev alence rates of 51% for cataract and 18% for glaucoma. Their screening methods were dif ferent from those employed in this study and in addition they included cognitively im paired residents.…”
Section: Discussionmentioning
confidence: 94%
“…However, in this later study reduced vision was taken as best corrected 6/9 or worse and thus direct comparisons are not possible. A similar study from England re ported a high prevalence of reduced vision in the over 75 year age group [3], A study of one hundred residents of old peoples homes re vealed a 51 % prevalence of cataract and un recognised significant refractive errors were present in 34% [4], Vision of 6/18 or less is usually taken as sufficient impairment to have difficulty watching television and is well be low the legal requirement to drive (6/10).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of care home residents have reported high prevalence rates of vision problems both in the UK 118 and in Australia. 119 It has been suggested that VI may be a contributory factor to older people being placed in care homes.…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11] Studies suggest that vision impairment in about one-third of nursing home residents could largely be reversed by treatment of uncorrected refractive error (myopia, hyperopia, presbyopia). 4,12 There are several factors that could be contributing to these high vision impairment rates. Persons with vision impairment are more likely to be admitted to nursing homes as compared with those with normal sight.…”
mentioning
confidence: 99%